Stabilizing Fluorine–π Interactions. (2nd May 2017) - Li, Ping; Maier, Josef M.; Vik, Erik C.; Yehl, Christopher J.; Dial, Brent E.; Rickher, Amanda E.; Smith, Mark D.; Pellechia, Perry J.; Shimizu, Ken D.
Abstract: A series of N ‐arylimide molecular balances were designed to study and measure fluorine–aromatic (F–π) interactions. Fluorine substituents gave rise to increasingly more stabilizing interactions with more electron‐deficient aromatic surfaces. The attractive F–π interaction is electrostatically driven and is stronger than other halogen–π interactions.